Оптимізація узгодження сигналів з багатоканальними системами - Незнанов, М. Ю. (ХНУРЕ, 2023)
Object of research is multichannel data transmission system with crosstalks. Purpose is to create the tools and implementation for the linear multiple channels to minimize mutual influences of the circuits and also minimize the reflection back from the receiver. The criteria and optimization program for constructing the best operating channels were developed.
Keywords: неоднорідний багатопровідний канал; узагальнена система телеграфних рівнянь; сторонні сигнали